The Relationship between Anger Rumination and Aggression in National Iranian Athletes - Mohammad Ali Besharat; Asma Hoseini (University of Tehran, 2010)
This study aimed to examine the relationship between anger rumination and aggression in a sample of Iranian athletes. A correlational analysis was performed to assess the kind of association between four subscales of anger rumination (angry afterthoughts, thoughts of revenge, angry memories, and understanding of causes) and different aspects of competitive aggression and aggressive behavior including physical aggression, verbal aggression, anger, hostility, and indirect aggression. A total of 210 volunteer athletes (132 males, 78 females) from different Iranian sport federations were selected for this study. All participants were requested to complete the Persian version of the anger rumination scale (FARS) and the Competitive Aggression Questionnaire (CAQ). The results revealed that anger rumination subscales were positively associated with indices of competitive aggression. Anger rumination distracted using learned sport skills and techniques through weakening anger management and caused competitive aggression. Anger rumination also increased the possibility of aggressive behavior through distracting concentration on performing sport skills and techniques. Based on the findings of the present study, it can be concluded that anger rumination during competitive sports can cause aggressive behavior and reduce the possibility of sport achievements.